POLA PEMBERIAN MAKAN ANAK (6-18 BULAN) DAN HUBUNGANNYA DENGAN PERTUMBUHAN DAN PERKEMBANGAN ANAK PADA KELUARGA MISKIN DAN TIDAK MISKIN - Vita Kartika; Sri Prihartini; Syafrudin Syafrudin; Abas B. Jahari (Persagi, 2000)
PATTERNS OF CHILD FEEDING (6-18 MONTHS OLD) FROM POOR AND WELL OFF FAMILIES AND THEIR RELATIONSHIP WITH CHILD GROWTH AND DEVELOPMENT.Background: A research was conducted on children of 6-18 month old from poor and well off family at Ciomas Sud-district, Boger Regency, West Java.Objective: This research aimed at observing the influence of feeding pattern of child under 2 years in its relation to child growth and development of the two family groups.Method: Sampling was conducted purposively amounted to 55 children from the poor families and 36 children from well of families, so the total is 91 children. Data was analyzed statistically by using SPSS program, with chisquare and T statistical test to find out the relationship among variabels.Results: From the result of this research it was found out that there are 44 children from the poor families who were only feed with carbohydrate, and the other 11 had a complete feeding pattern (carbohydrate + protein). Meanwhile, of the 36 children of well off families, 30 (83%) have the complete feeding pattern and 6 (17%) have the carbohydrate only feeding pattern. From the result of growth measuring calculated based on nutrient status (weight/age) there were 15 of 55 children from the poor families who were undernourished, those who had thecarbohydrate only feeding pattem,i.e. 10 children (66.7%). Whereas of the 36 children from well families, therewere 34 with good nutrient status, and 2 undernourished children. Statistical test shows that there is a significant difference of feeding pattern and growth between the two family groups (p<0.05). Observing the rough motoric development, there were 28 children with slowness at the beginning of the research, i.e. 25 children from the poor families and 3 from the well off families. However, six month after the activity was carried out, there was a change on 3 children from the well of families to be normal, while from the poor families only 3 children that changed to normal.Conclusions: Statistical test shows that there is a significant difference between the motoric development and feeding pattern on the two family groups both at the beginning and the end of the research.Key Words: feeding pattern, children under 2 years